Socio-environmental factors related to leishmaniasis at the cantonal level, Costa Rica, 2018-2021 - Elizondo-Morales, Armando; Fernández-Córdoba, Andrés; Soto-Trejos, Laura; Paniagua-Hidalgo, Diana María (Horizonte Sanitario, 2024)
Objective: Analyze socio-environmental factors related to the cumulative incidence of leishmaniasis at the cantonal level in Costa Rica from 2018 to 2021.Materials and methods: Observational, ecological, cantonal, descriptive-analytical study. A spatial analysis is carried out through choropleth maps, Moran Index and Local Spatial Association Index. Bivariate and multivariate negative binomial regression models are carried out.Results: Two multivariate models are developed: Multivariate model A: the variables educational dimension and access to information behave as protective factors. Model B: the percentage of households lacking decent shelter, sex ratio, percentage of Afro-descendant population and percentage of poor households act as risk factors.Conclusions: It is observed that the cantons with the highest cumulative incidence of leishmaniasis were those located mainly in the Caribbean and southern areas.Socio-environmental factors related to the cantonal standardized cumulative incidence of leishmaniasis in Costa Rica from 2018 to 2021 are identified.It is possible to determine the presence of clusters of high spatial autocorrelation between the variables identified in this research as protective factors educational dimension, access to information and risk factors percentage of households lacking decent shelter, sex ratio, percentage of population Afro-descendant, and percentage of poor households mainly in cantons located in the Caribbean area and southern part of the country, as well as clusters of low spatial autocorrelation in cantons in the center of the country. Keywords: Leishmaniasis; Epidemiology; Spatial analysis.